A new species of Galumnella (Acari, Oribatida, Galumnellidae) from Mozambique - Ermilov, Sergey G.; Bąkowski, Marek (Zootaxa, 2021)
The present study is based on oribatid mite materials collected from Mozambique in 2019. A list of identified taxa, including 53 species/subspecies from 44 genera and 28 families is provided. Of these, six species are new to science, all other taxa are recorded for the first time in the Mozambican fauna. One new species, Galumnella mikhailovi Ermilov sp. nov., is described herein: it is similar to G. csavasorum in the presence of setiform, unilaterally spinose bothridial setae and rugose notogaster, but differs in smaller body size, the presence of monodactylous legs and rounded rostrum, as well as in the absence of sublamellar line and rugose sculpturing in the anogenital region.